(untitled) (Journal of Geography and Environmental Management, 2023)
In the article the results of assessment of the changes in the air temperature, sums of precipitation, and the snow depth in the Arys River basin, which is the right tributary of the Syrdarya River are presented. In the context of global warming, noticeable changes are taking place in mountains, and the risk of hazards associated with snow, glaciers and permafrost is growing. In the upper reaches of the Arys River basin, strong snowmelt-rain floods occur against the backdrop of a thaw. It is necessary to study the climatic factors influencing the state of the mountain cryosphere. Based on the data of ground observations carried out by the Kazakh Hydrometeorological Service at the meteorological stations and according to the data of total precipitation gauges and field snow surveys in the mountains, the changes in the characteristics of the winter period for 1960-2023 are shown. The results of the analysis made it possible to estimate the increase in the average air temperature for the year and the cold period at 0.1°C/10 years. There is a slight increase in the sums of precipitation for November-March. The average snow depth, according to the field snow surveys, has increased by 5–20 cm. Over the past 30 years, the amount of snow-water equivalent has increased compared to the period of 1960–1990 at almost 80-100% of measurement points. The dates of occurrence of the snow cover have shifted towards somewhat earlier start and finish dates. The results of the analysis made it possible to identify changes in the mean multiyear meteorological characteristics over two 30-year periods.